Novel Technology for Phenol Wastewater Treatment Using Electrochemical Reactor - Yuncheng Xie; Ning Jiang; Wei Guan; Fangying Ji; Zhigang Xie; Jing Zhang (Journal of Chemistry)
There are various electrochemical approaches to save energy, mostly by means of equipment improvement coupled with other water treatment technologies. Replacement of DC power with pulse power, modified reactor coupled with photocatalysis can decrease cost. But more or less additional input is developed, or infrastructure has to be replaced. In this paper, an N-Step electrochemical reactor, based on stage reaction modeling, is put forward. On the basis of not changing equipment investment and by adjustment of the operating current density at different levels, power consumption decreases. This model develops a foundation of electrochemical water treatment technology for the engineering application.